2010
DOI: 10.1126/science.1194653
|View full text |Cite
|
Sign up to set email alerts
|

Tau Reduction Prevents Aβ-Induced Defects in Axonal Transport

Abstract: Amyloid-β (Aβ) peptides, derived from the amyloid precursor protein, and the microtubuleassociated protein tau are key pathogenic factors in Alzheimer's disease (AD). How exactly they impair cognitive functions is unknown. Here we assessed the effects of Aβ and tau on axonal transport of mitochondria and the neurotrophin receptor TrkA, cargoes that are critical for neuronal function and survival and whose distributions are altered in AD. Aβ oligomers rapidly inhibited axonal transport of these cargoes in wildt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
369
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(400 citation statements)
references
References 12 publications
24
369
0
1
Order By: Relevance
“…Neuronal axon–Schwann cell interaction(s) are essential for myelination, and myelin maintenance is a dynamic process tightly controlled by axon‐dependent transcription factors such as Krox20 and Oct6 (Murphy et al ., 1996; Decker et al ., 2006). In line with previous studies demonstrating an absence of axonal deficits in neurons of Tau−/− animals (Yuan et al ., 2008; Vossel et al ., 2010), there were no differences in mRNA levels of transcription factors that critically regulate myelination process and/or maintenance, for example, Krox20 and Oct6 (data not shown), suggesting no gross changes in myelin gene regulation of Tau−/− Schwann cells. Furthermore, supporting the involvement of Tau and other cytoskeletal elements in myelination process, previous evidence suggests that Tau strongly colocalizes with MBP in distal tips of oligodendrocytes (LoPresti et al ., 1995; Muller et al ., 1997), suggesting that transportation and/or local MBP translation may require microtubule cytoskeleton and might be controlled by Tau–Fyn interaction (Klein et al ., 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Neuronal axon–Schwann cell interaction(s) are essential for myelination, and myelin maintenance is a dynamic process tightly controlled by axon‐dependent transcription factors such as Krox20 and Oct6 (Murphy et al ., 1996; Decker et al ., 2006). In line with previous studies demonstrating an absence of axonal deficits in neurons of Tau−/− animals (Yuan et al ., 2008; Vossel et al ., 2010), there were no differences in mRNA levels of transcription factors that critically regulate myelination process and/or maintenance, for example, Krox20 and Oct6 (data not shown), suggesting no gross changes in myelin gene regulation of Tau−/− Schwann cells. Furthermore, supporting the involvement of Tau and other cytoskeletal elements in myelination process, previous evidence suggests that Tau strongly colocalizes with MBP in distal tips of oligodendrocytes (LoPresti et al ., 1995; Muller et al ., 1997), suggesting that transportation and/or local MBP translation may require microtubule cytoskeleton and might be controlled by Tau–Fyn interaction (Klein et al ., 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Tau absence confers neuroprotection in several models of neuronal damage, such as traumatic brain injury (Cheng et al , 2014), neuroinflammation (Maphis et al , 2015), amyloid β‐mediated excitotoxicity (Roberson et al , 2007, 2011; Ittner et al , 2010; Vossel et al , 2010), and epilepsy (Holth et al , 2013), among others. Given that acute stress negatively affects AHN (Gould et al , 1992) and considering the neuroprotection exerted by the lack of Tau in the aforementioned models, we addressed whether the Porsolt test would cause similar detrimental effects in Tau −/− and WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tau knockout studies revealed that the Aβ-induced axonal transport deficits and impairment of hippocampal LTP were mediated by tau [58,59]. Reduction of endogenous tau was also shown to ameliorate cognitive behavioral deficits and the death rate of APP overexpressing mice [60][61][62].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%